AIDS between science and politics - Piot, Peter, 1949- (EBL-Schweitzer, 2014)
This title recounts the experiences of the founding executive director of the Joint United Nations Programme on HIV/AIDS (UNAIDS) as he fought the disease from its earliest manifestations to today. It describes how the HIV/AIDs epidemic altered global attitudes toward sexuality, changed the character of the doctor-patient relationship, altered the influence of civil society in international relations and broke traditional partisan divides. It illustrates how AIDS thrust health into national and international politics.